No place to run : the Canadian Corps and gas warfare in the First Wold War - Cook, Tim, 1971- (UBC Press, 1999)
"Historians of the First World War have often dismissed the importance of poison gas in the battles of the Western Front. No Place to Run shows that this chemical plague was a serious threat even after gas masks were introduced." "Tim Cook uses diaries, letters, reminiscences, published memoirs, and the official archival record to illustrate vividly the grim reality of gas warfare for the average trench soldier. In response, the Canadian Corps had to develop a disciplined anti-gas doctrine, a process that Cook describes in full." "No Place to Run provides a challenging re-examination of the function of gas warfare in the First World War, including not only its important role in delivering victory in the campaigns of 1918 but also its postwar legacy."--Jacket